BCNO Nanosheet Supported Co3O4 Nanoparticles as an Enhanced Electrocatalyst for Oxygen Evolution Reaction. Issue 6 (29th March 2019) - Ji, Xuefeng; Li, Yingxin; Jia, Xiaobo; Yang, Xiaojing; Li, Lanlan; Yao, Yingwu; Cheng, Yahui; Zhang, Xinghua; Lu, Zunming; Liu, Hui
Abstract : Cobalt trioxide is a promising cobalt-based oxygen evolution reaction (OER) electrocatalyst, and its OER performance is limited by its low ratio of Co 3+ to Co 2+ ions and the dispersibility of nanoparticles. Here we report a simple method to improve the OER catalytic activity via loading Co3 O4 nanoparticles onto boron carbon oxynitride (BCNO) nanosheets, which greatly decreases the overpotential (∼80 mV) and improves the stability of the Co3 O4 nanoparticles. The Co3 O4 /BCNO nanocomposite exhibits a good OER performance with a small Tafel slope of 57.58 mV/dec and a low overpotential of 317 mV (vs RHE at 10 mA/cm 2 ) under alkaline conditions. The high OER performance of the Co3 O4 /BCNO nanocomposite is induced by the larger active surface area and higher ratio of Co 3+ to Co 2+ ions as well as the formation of Co-N chemical bonds.